Foregrounding Socioeconomic Rights in Transitional Justice: Realising Justice for Violations of Economic and Social Rights. Issue 2 (June 2014) - Cahill-Ripley, Amanda
Transitional justice has traditionally ignored or sidelined violations of economic and social rights, focussing on violations of civil and political rights as the primary grave human rights violations to be addressed when seeking justice for past atrocities. This paper explores the omission of these rights from the field and uncovers the shortcomings of such an approach. It will argue that there is a need for transitional justice to address both deliberate violations of economic and social rights resulting from conflict or repression, but also structural violations which have acted as root causes of conflict within the State. It is submitted that past experiences of prosecutorial and restorative justice illustrate that violations of economic and social rights have been acknowledged as background information rather than primary concerns for transitional justice. In conclusion it is contended that economic and social rights need to be brought to the foreground of transitional justice processes in order to ensure effective transitional justice which reflects the needs and rights of the local population, and addresses the root causes of conflict, thus preventing conflict reoccurring around the same sources. The inclusion of economic and social rights concerns within transitional justice mechanisms will therefore contribute to a more holistic and inclusive transitional justice process.